Beach nourishment project of Seberang Perai Utara beach, Butterworth, Malaysia: a case study / Mohd. Masri Mohd. Hajazi - Mohd. Hajazi, Mohd. Masri (1992)
Beach nourishment is & technique for shoreline stabilization and storm protection. It is very attractive as a recreational value to an important coastal tourism industry and has become increasingly popular as a method of shoreline protection in Malaysia nowadays. This project starts with an explanation of the data required to study the beach condition. These data are taken from a beach nourishment project in Seberang Perai Utara. The study area of this project is along a 25Om stretch of Robina Park beach which is 1O km from the Butterworth Cargo Terminal. Secondly, a study is made on the method of design beach nourishment. The data from Seberang Perai Utara project are used to show the design calculation. Thirdly, a comparison between the sample calculation and the result of the actual Seberang Perai project is made to check the accuracy of the design methodology . Lastly, the study is concluded with on the construction method used in beach nourishment.